2013
DOI: 10.1055/s-0033-1337943
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Training in Elite Soccer Players: Systematic Bias between Running Speed and Metabolic Power Data

Abstract: We compared measurements of high-intensity activity during field-based training sessions in elite soccer players of different playing positions. Agreement was appraised between measurements of running speed alone and predicted metabolic power derived from a combination of running speed and acceleration. Data was collected during a 10-week phase of the competitive season from 26 English Premier League outfield players using global positioning system technology. High-intensity activity was estimated using the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
192
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(219 citation statements)
references
References 14 publications
(28 reference statements)
19
192
2
6
Order By: Relevance
“…The current study is the first to differentiate players into the five positional roles. Similar to previous studies in soccer (10,17,21,37) , rugby league (5,6,20) and Australian football (2,15,16,19) positional differences for running performance during elite Gaelic football were observed. Specifically, midfielders covered greater total distance compared to other playing positions, also high speed distances were greater for midfielders as well as half-forwards and half-backs in comparison to full-forwards and full-backs.…”
Section: A C C E P T E Dsupporting
confidence: 90%
“…The current study is the first to differentiate players into the five positional roles. Similar to previous studies in soccer (10,17,21,37) , rugby league (5,6,20) and Australian football (2,15,16,19) positional differences for running performance during elite Gaelic football were observed. Specifically, midfielders covered greater total distance compared to other playing positions, also high speed distances were greater for midfielders as well as half-forwards and half-backs in comparison to full-forwards and full-backs.…”
Section: A C C E P T E Dsupporting
confidence: 90%
“…Nonetheless, the association between high-speed running (total and relative), relative total distance, total metabolic power and relative high power distance with RPE-L was moderate, which we believe provides further support for the discriminate validity of differential RPE's. The incorporation of both velocity and acceleration contributions to external load using the metabolic power approach did not strengthen associations with RPE ratings, which supports recent conclusions drawn by Coutts et al 21 who suggested that metabolic power adds little information to external loading observations in AFL matchplay, perhaps due to the less congested nature of AFL versus Soccer 17,20 or Rugby League. 28 The unclear associations between accelerometer derived indices and RPE ratings may reflect the large between-subject variation in running mechanics.…”
Section: Discussionsupporting
confidence: 75%
“…However, total energy costs calculated from this model are similar to those derived from physiological measures, 17 and its determination of the instantaneous metabolic cost has demonstrated concurrent 19 and construct validity. 20,21 Therefore, in this study we adopted the metabolic power approach to estimate total match energy expenditure (Energy Expenditure, KJ·kg -1 ) and average metabolic power (Pmet, W·kg -1 ), together with the relative distance covered at a high instantaneous metabolic power (≥ 20 W·kg -1 ). Equivalent Distance (ED; m) was determined to represent the corresponding total distance covered for steady state running to match the estimated energy expenditure.…”
Section: Technical [Rpe-t])mentioning
confidence: 99%
“…Metabolic power estimations adjust data to incorporate the additional energy cost of acceleration and deceleration activities [27]. Although no studies have yet been conducted, these measures could be a valid means for interpreting changes in performance and subsequently individualising recovery strategies according to a more accurate account of the match loads imposed on players [28]. Indeed, recent research using global positioning systems (10 Hz sampling) in elite players has shown that the distance covered in rapid acceleration/deceleration phases is potentially more sensitive than high-speed distance alone in detecting variations in match running performance [29].…”
Section: Additional Running Performance-related Analysesmentioning
confidence: 99%